Fluorescent Flippers for Mechanosensitive Membrane Probes - Dal Molin, Marta (J Am Chem Soc, 2015)
[Image: see text] In this report, “fluorescent flippers” are introduced to create planarizable push–pull probes with the mechanosensitivity and fluorescence lifetime needed for practical use in biology. Twisted push–pull scaffolds with large and bright dithienothiophenes and their S,S-dioxides as the first “fluorescent flippers” are shown to report on the lateral organization of lipid bilayers with quantum yields above 80% and lifetimes above 4 ns. Their planarization in liquid-ordered (L(o)) and solid-ordered (S(o)) membranes results in red shifts in excitation of up to +80 nm that can be transcribed into red shifts in emission of up to +140 nm by Förster resonance energy transfer (FRET). These unique properties are compatible with multidomain imaging in giant unilamellar vesicles (GUVs) and cells by confocal laser scanning or fluorescence lifetime imaging microscopy. Controls indicate that strong push–pull macrodipoles are important, operational probes do not relocate in response to lateral membrane reorganization, and two flippers are indeed needed to “really swim,” i.e., achieve high mechanosensitivity.